Experience of surgical management of rare cases of choledochal cyst in last five years—tertiary care reflection - Mohammad Sohail Asghar; Sabir, Zainab; Zaman, Balakh Sher; Zafarullah, Sadaf; Hafiz Syed Zaigham Ali Shah; Aslam, Imran; Afzal, Ameer (Journal of the Pakistan Medical Association, 2023)
Choledochal Cyst (CC), also known as the biliary cyst, is one of the rare inherited anomalies of intrahepatic and/or extrahepatic biliary system characterised by varying degrees of cystic dilatation of the biliary tract without acute obstruction. The prevalence ranges from 1 in 13,000 people to 1 in 2 million people with preponderance in Asia (1), particularly in Japan. Moreover, the presentation also varies in children and adults, and is usually vaguer and non-specific in adults. The prevalence is even lower in males, with female to male ratio being 3:1-4:1 (2). We present here three cases of adult choledochal cysts excised in our surgical unit in the last five years. We discuss the aetiopathogenesis, presentation, diagnosis, surgical treatment, and complications of choledochal cysts based on the available literature. —Continue